2022
DOI: 10.1002/ldr.4470
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Camellia oleifera cultivation influences the assembly process of soil bacteria in different soil aggregate particles

Abstract: Understanding the mechanisms that govern microbial community assembly across a soil-plant continuum is crucial for predicting the responses of ecosystems to environmental changes. However, the impact of the health status of plants on microbial assemblies across these continuums remains poorly understood. In this study, we investigated the stochastic and deterministic processes associated with different aggregate particles and Camellia oleifera growth stages (sapling, maturity, and degeneration periods). The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Continuous application of organic and inorganic fertilizers could promote the bacterial diversity in the C. oleifera rhizosphere. Different treatments promote the richness of eutrophic bacteria and inhibit the richness of hypotrophic bacteria (Lijun et al, 2022). In this research, PCoA revealed that bacterial community composition had significant differences among the six fertilization treatments.…”
Section: Effects Of Soil Chemical Properties On the Rhizosphere Bacte...mentioning
confidence: 59%
“…Continuous application of organic and inorganic fertilizers could promote the bacterial diversity in the C. oleifera rhizosphere. Different treatments promote the richness of eutrophic bacteria and inhibit the richness of hypotrophic bacteria (Lijun et al, 2022). In this research, PCoA revealed that bacterial community composition had significant differences among the six fertilization treatments.…”
Section: Effects Of Soil Chemical Properties On the Rhizosphere Bacte...mentioning
confidence: 59%
“…A meta-analysis of 125 works of literature found that a tea (Camellia sinensis) monoculture plantation can cause a decline in biodiversity, while traditional rustic tea agroecosystems have the potential to support a greater amount of wildlife [20]. Previous studies have demonstrated that an oil tea plantation influences the community assembly of soil microorganisms [21,22], while its impact on local fauna remains poorly understood. In particular, seed-caching rodents have been identified as crucial contributors to the seed fate of oil tea plants, playing a key role in shaping their regeneration process [17,23].…”
Section: Introductionmentioning
confidence: 99%